Stability and Infectivity of SARS-CoV-2 and Viral RNA in Water, Commercial Beverages, and Bodily Fluids - Fukuta, Mizuki; Mao, Zhan Qiu; Morita, Kouichi; Moi, Meng Ling (Frontiers in Microbiology, 2021)
The stability and infectivity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in liquid samples is great concern on virus transmission via common beverages and sewage water. Here we investigated the stability of SARS-CoV-2 in 32 liquids including common beverages, bodily fluids and commonly used viral transport media. Our results showed that infectious virus could be recovered up to 77-days from common beverages including milk and water. Viral RNA could be detected at high levels in all samples up to 28-days, indicating that while viral RNA demonstrates higher stability than infectivity, viral RNA levels do not reflect the infectious capability of SARS-CoV-2. These results indicate that SARS-CoV-2 is highly stable in optimal conditions and a sufficient control measure is needed in reducing the risk of exposure and, controlling and preventing future outbreaks.